Unmet Birth Expectations and Birth Trauma among Adolescents. Issue 1 (January 2022) - Anderson, Cheryl A.; Akinmade, Faith
Abstract: Purpose: To assess and compare birth expectations of younger and older age adolescents and explore if unmet expectations predict psychological birth trauma (PBT). Study Design and Methods: This secondary analysis expands findings of a previous study ( N = 303) which classified adolescents' perceptions of birth into four main themes. The previous study used a mixed-methods approach providing data related to birth expectations. For the current study, expectations were determined by themes as met or unmet by three reviewers. Of 116 useable written narrations, responses of younger (ages 13-17) versus older (ages 18-19) adolescents were compared and explored for impact on PBT. Results: Birth expectations for both age groups were more often unmet than met. Despite a smaller cohort, younger adolescents provided more remarks than older adolescents. There were no differences between groups on unmet birth expectations ( p = .16). Unmet expectations most often related to pain with older adolescents more inclined to state poor pain management. Younger adolescents more often feared dying. Unmet expectations did not predict PBT. Clinical Implications: Comprehensive prenatal care can allow for early, open conversations to assess labor knowledge and misconceptions, fear of birth, existing supports, and overall birth expectations, with a premier focus on expected labor pain and pain management. Multiparous adolescents should receive prenatal assessments of posttraumatic stress (PTS) symptoms (a recognized predictor of posttraumatic stress syndrome) potentially originating from a previous traumatic birth. Following birth, symptoms of acute stress and PTS should be assessed of all adolescents, especially if experienced numerous unmet labor expectations. Abstract : Giving birth as a teenager can be stressful and frightening. Adolescents have many unmet expectations during childbirth including labor support and pain relief. In this study of adolescents surveyed during their inpatient postpartum hospitalization, birth expectations were more often unmet than met. Older adolescents' unmet expectations most often related to inadequate pain management while younger adolescents feared dying. Unmet expectations did not predict psychological birth trauma.